A nonlinear control strategy for fuel delivery in PEM fuel cells considering nitrogen permeation. (12th January 2017) - Hong, Ling; Chen, Jian; Liu, Zhiyang; Huang, Lianghui; Wu, Zhongle
Abstract: Hydrogen energy shows its great potential to be one of the future sustainable energies with abundant storage and high energy content. Proton exchange membrane (PEM) fuel cells, as a hydrogen energy conversation plant with high efficiency, becomes a hot topic of many researches. This paper proposes a multi-input-multi-output (MIMO) nonlinear control strategy for fuel delivery in PEM fuel cell systems. Specifically, a control oriented dynamic model is developed for the fuel delivery system (FDS) with anode recirculation and anode bleeding. Based on the model, a MIMO nonlinear state feedback controller is proposed to maintain adequate hydrogen supply and suitable anode hydrogen concentration. Moreover, an optimized output feedback controller is proposed to improve the state feedback controller, where the unknown hydrogen partial pressures utilized are estimated by developed observers. Lyapunov based stability analysis is carried out to analyze the proposed output feedback controller and the observers. Simulation results show the effectiveness of the proposed controller under various current demands.